Rock type discrimination using Landsat-8 OLI satellite data in mafic-ultramafic terrain - Tamilarasan, Kuppusamy; Anbazhagan, Siddan; Ranjithkumar, Sundararajan (Geology, Geophysics and Environment, 2023)
The mafic-ultramafic terrain of the Bhavani complex in southern India is considered for lithological mapping. The Landsat-8 OLI satellite data was used for the interpretation of different rock types in the study area. The satellite data were digitally processed using ENVI 5.6 image processing software. In the OLI data, excluding bands 8 and 9, the remaining seven bands were used for the generation of colour composite images, band ratios, principal component analysis and SVM classification. Reflectance spectral measurements were carried out in laboratory conditions for five rock samples collected from the study area. The XRF analysis was carried out to estimate the composition of major oxides present in the rock samples. The results obtained from XRF analysis were compared with the rock spectra in characterizing the spectral features of the rock types. The colour composite images (B543, B567, B456, and B457), PCA composite image (PC312 and PC456), band ratios (BR5/5 and BR4/3), colour composite images from band ratios, and SVM classified output are useful in delineation various rock types in the terrain.